Recognising the academic and political purposes embedded in history textbook assessment tasks (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This paper explores the nature of history as a school-based discipline and how history is recontextualised in the South African History Curriculum and Assessment Policy Statement (CAPS) and Grade 10 history textbooks, with a particular focus on what the assessment activities and questions require of learners. The conceptual tools used in this document analysis were inspired by Morgan and Henning (2013) and came from Wertsch (2002), Anderson (2005) and Krathwohl (2002). The findings indicate that within the ‘doing school history’ construct, there is both an academic and a political dimension. These two projects may appear to be at odds with one another, but we argue that the study of history is strengthened when both are given their due respect.
Keywords: Knowing history; Doing history; History textbook assessment tasks; Source-based tasks; Academic project; Political project; Collective memory; Historical thinking